Temporal changes in postprandial blood transcriptomes reveal subject-specific pattern of expression of innate immunity genes after a high-fat meal - Lemay, Danielle G; Huang, Shurong; Huang, Liping; Alkan, Zeynep; Kirschke, Catherine; Burnett, Dustin J; Wang, Yining E; Hwang, Daniel H (The Journal of nutritional biochemistry, 2019)
White blood cells are among the first responders to dietary components and their metabolites absorbed from the gut. The objective of this study was to determine the whole blood transcriptome response to high-fat challenge meals. A total of 45 fasting and postprandial (3-h and 6-h) whole blood transcriptomes from 5 subjects in a crossover intervention trial of a high-fat meal supplemented with placebo, blueberry powder or docosahexaenoic acid (DHA) were analyzed using RNA sequencing. Select target genes were validated by quantitative reverse-transcription polymerase chain reaction in 180 samples from 20 subjects. The largest contributor to variance was the subject (13,856 genes differentially expressed), followed by the subject on a specific day (2276 genes), followed by the subject's postprandial response (651 genes). After determining the nonsignificance of individual dietary treatments (blueberry, DHA, placebo), treatments were used as replicates to examine postprandial responses to a high-fat meal. The universal postprandial response (95 genes) was associated with lipid utilization, fatty acid beta-oxidation and circadian rhythms. Subject-specific postprandial responses were enriched for genes involved in the innate immune response, particularly those of pattern recognition receptors and their downstream signaling components. Genes involved in innate immune responses are differentially expressed in a subject-specific and time-dependent manner in response to the high-fat meals. These genes can serve as biomarkers to assess individual responsiveness to a high-fat diet in inducing postprandial inflammation. Furthermore, the dynamic temporal change in gene expression in postprandial blood suggests that monitoring these genes at multiple time points is necessary to reveal responders to dietary intervention.